Microbiocenosis of adenocarcinoma tissue in colon cancer patients with different preoperative preparation - N. I. Simonenko; E. Yu. Zlatnik; N. I. Panova; O. G. Shulgina; A. Yu. Maksimov (Южно-Российский онкологический журнал, 2023)
Purpose of the study. To assess the effect of inclusion of lactoglobulin in complex preoperative preparation of colon cancer patients on their tumor and resection line tissue microbiota.Materials and methods. 40 patients with colon cancer stages II–III, in whom the operation was the first stage of treatment, during standard preoperative preparation, were injected with a preparation of antibodies against opportunistic intestinal microorganisms obtained from colostrum of immunized cows, 2 g twice a day orally before surgery for 3 days (total dose of 12 g) (main group); 40 patients received standard antibiotic prophylaxis (control group). The quantitative composition of the microbiota was determined in the samples of the removed tumor and tissue of the resection line.Results. The total microbial contamination of the tumor was 9.2 times lower in the main group relative to the control group; the frequency of E.coli and Clostridiae excretion was also statistically significantly lower (p = 0.004 and 0.03, respectively). In the tumors of patients of the main group out of twelve studied representatives of microorganisms, the number of six was statistically significantly lower than in control group, and three of those found in the control group were not detected. Since they were potentially pathogenic (Pseudomonas aeruginosa, Staphylococcus aureus, fungi of the Candida spp.), the microbial composition of the tumor of patients in the main group can be considered more favorable than the control group. Similar differences were noted in non-t umor intestinal tissue, in which the content of Enterobacter spp, Streptococcus, Clostridiae, Peptostreptococci was statistically significantly lower than in the control group.Conclusion. Thus oral administration of colostrum antibodies caused positive changes in tumor and colon tissue microbiota. We suggest the application of lactoglobulin to be useful for surgical treatment of such patients taking into account the possible impact of microbiota in patients’ response to chemo- and immunotherapy.